Parental Digital Media Habits Correlated with Time Spent on Digital Media among Preschool Children - Widya Hary Cahyati; Lukman Fauzi; Tandiyo Rahayu; Michael Yong Hwa Chia (Journal of Nonformal Education, 2024)
Recently, the use of digital media has increased significantly. The role of parents is very important in the use of digital media for children. The aim of this study is to determine the correlation between parental digital media and physical play habits with time spent on digital media by preschool children aged 2-6 years in Semarang City, Indonesia. The benefits of this research are as a reference for the use of digital media for parents in child care. The novelty of this research is an analysis of the use of digital media on children's physical activity. It was cross sectional study to 360 parents who had preschool children and voluntarily complete the validated online questionnaire. Data were collected using the Surveillance of digital-Media hAbits in earLy chiLdhood Questionnaire (SMALLQ®). We analyzed the data collected with Spearman test. The result showed that the time spent on digital media by parents positively correlated with time spent on digital media by children on weekday (p value<0.01) and on weekend (p value<0.01). Digital media engagement with children negatively correlated with time spent on digital media by children on weekday (p value: 0.03) and on weekend (p value: 0.02). However, physical play engagement with children do not correlate with time spent on digital media by children on weekday (p value: 0,71) and on weekend (p value: 0,35). Conclusion, time spent on digital media by parents and digital media engagement correlated with time spent on digital media by preschool children aged 2-6 years old.